The consumer on the payment market in Poland – preferred payment methods (Economic and Political Thought, 2022)
The aim of the article is to analyze selected available payment methods and their preferences among consumers on the Polish market. Work hypothesis: the main determinants influencing the choice of payment method are convenience, security and speed of transactions. In order to verify the hypothesis, the literature on the subject was reviewed, legal acts as well as industry studies were analyzed. Moreover the own questionnaire research was conducted. The results of the research confirm the truth of the hypothesis put forward at the beginning of the article.
Keywords: payments, payment services, payment habits, BLIK